2014
DOI: 10.1371/journal.pone.0098369
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Health Is a More Important Determinant for Diabetes Development than Simple Obesity: A 4-Year Retrospective Longitudinal Study

Abstract: BackgroundRecent studies report the importance of metabolic health beyond obesity. The aim of this study is to compare the risk for diabetes development according to different status of metabolic health and obesity over a median follow-up of 48.7 months.Methods6,748 non-diabetic subjects (mean age 43 years) were divided into four groups according to the baseline metabolic health and obesity status: metabolically healthy non-obese (MHNO), metabolically healthy obese (MHO), metabolically unhealthy non-obese (MUH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
4
38
0
1
Order By: Relevance
“…However, some obese people do not suffer from the common metabolic disturbances related to obesity, adopting the concept of metabolically healthy obesity (MHO) . Similarly, some non‐obese people are at risk of NAFLD‐related outcomes in opposite to other non‐obese subjects with a few metabolic factors . There is no general agreement on the criteria to define the metabolically healthy status, although most of the studies focus on subjects with two or fewer metabolic components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some obese people do not suffer from the common metabolic disturbances related to obesity, adopting the concept of metabolically healthy obesity (MHO) . Similarly, some non‐obese people are at risk of NAFLD‐related outcomes in opposite to other non‐obese subjects with a few metabolic factors . There is no general agreement on the criteria to define the metabolically healthy status, although most of the studies focus on subjects with two or fewer metabolic components.…”
Section: Introductionmentioning
confidence: 99%
“…11 Similarly, some non-obese people are at risk of NAFLD-related outcomes in opposite to other non-obese subjects with a few metabolic factors. 12 There is no general agreement on the criteria to define the metabolically healthy status, although most of the studies focus on subjects with two or fewer metabolic components. Hence, these concepts have been evaluated for vascular function, 13 ischaemic stroke, 14 myocardial ischaemia, 15 or chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic health is a more important determinant for diabetes development than simple obesity [43]. Diabetes was the most common metabolic condition in our patients, present in 38% of subjects.…”
Section: Discussionmentioning
confidence: 74%
“…19,20 Rhee et al compared CAC scores assessed by MDCT among 24,000 participants with different metabolic health and obesity statuses; CAC levels were similar for both non-obese but metabolically unhealthy individuals and metabolically unhealthy obese paticipants. 12 This finding suggests that metabolic health is more closely associated with CAC than obesity via a complex pathway. 12 Recently, after studying the CT scans of 276 participants scoring multiple arteries, including the coronary arteries and aorta, Takx et al reported the systemic nature of cardiovascular calcifications, with a weak link between BMI and cardiovascular calcifications among different arterial beds.…”
Section: -13mentioning
confidence: 99%
“…12 This finding suggests that metabolic health is more closely associated with CAC than obesity via a complex pathway. 12 Recently, after studying the CT scans of 276 participants scoring multiple arteries, including the coronary arteries and aorta, Takx et al reported the systemic nature of cardiovascular calcifications, with a weak link between BMI and cardiovascular calcifications among different arterial beds. 21 With regards to the relationship between PFV, vascular calcification and obesity, considerable evidence supports the vital role of pericardial fat accumulation in the coronary atherosclerosis process via the secretion of hormones and cytokines that modulate coronary artery haemostasis.…”
Section: -13mentioning
confidence: 99%